Composite Materials from Plant Fibers and Processed Plastic Waste for Exotic Knife Handles - Putra, Wawan Trisnadi; Mohamed, Saiful Bahri; Muhammad, Martini; Winangun, Kuntang; Munaji; Habibi, Jawad Sultan; Dwiprasetya, Chaesar Deserendy (International Journal of Community Service Learning, 2025)
This study developed an environmentally friendly composite material for exotic knife handles by utilizing plant fibers and recycled plastic waste. This study used an experimental method. This study aims to identify the best composition between natural fibers and recycled plastics that produce optimal mechanical and thermal properties while having high aesthetic value and comfort of use. This study is a research and development (R&D). The subjects involved in this study were natural materials in the form of plant fibers and recycled plastics. The population in this study included all possible combinations of fiber and plastic mixtures, while the samples were selected purposively. The data collection method was carried out through laboratory experiments with the composite material molding process using the compression molding method. The instruments used included mechanical test equipment, visual observation sheets, and questionnaires. The data analysis method was quantitative descriptive analysis for mechanical data and inferential statistical analysis. The results showed that the best composition was a mixture of 60% HDPE, 20% PP, and 20% coconut fiber with an HRB hardness value of 59.6 at a temperature of 280°C. In addition to the mechanical benefits, this study highlights the sustainability of the material and its economic potential in supporting local industries in Ponorogo. In conclusion, this study provides an innovative solution in plastic waste management while opening up new opportunities in the sustainability-based creative industry.